3D printing for fashion: new paradigms of desig nandconsumption (ModaPalavra e-periódico, 2020)
Thisworkaimedtotakeanapproachon3Dprintingtechnologyinthefashionsystem,andtheimportanceofpostponementstrategies,whichareleadingtogreaterinformationsharingintheproductionchainofthissector.ItisalsomentionateawaytointroducemasscustomizationbasedondigitalnetworksandotheremergingtechnologiesthathasbeenbreakingthetraditionalB2C(businesstoconsumer)paradigm.Thisstudyfeaturesthreeentry-levelmachinerydesignprojects,non-industrial3Dprinters,andissuesrelatedtonewwaysofconsumption.Itcanbeconcludedthat3Dprintingmanufacturingisassociatedwithleanproductionwithfewmaterialsurplusesorscraps,butwhenitcomestobuyingandshippingtheproducttheseissuesstillseemnottobeconsidered.
Keywords: 3D printing; fashion; consumption